3D interactive system based on vision computing of direct‐flective cameras. Issue 8 (6th July 2016) - Li, Xuan; Chen, Chun‐Ho; Huang, Yi‐Pai
Abstract: A bare‐finger 3D interactive technology for portable devices was developed. Using directive‐flective cameras to reform the field of viewing, a blind working range close to the camera is eliminated. Moreover, the algorithm of vision computing, different from skin color detection, is presented to determine the positions of fingertips. The interactive range is workable from 1.5 to 50 cm above the entire surface of the display. The mean position error of less than 1 cm is achieved. This accuracy realizes a camera‐based 3D interactive system allowing for near‐distance functionality. Therefore, floating 3D images can be touched and interacted with, potentially creating more application and intuitive user‐machine interface. Abstract : A bare‐finger 3D interactive technology for portable devices was developed. Using directive‐flective cameras to reform the field of viewing, a blind working range close to the camera is eliminated. Moreover, the algorithm of vision computing, different from skin color detection, is presented to determine the positions of fingertips.